Adaptive Channel Map for Time Slotted Channel Hopping Industrial Wireless Networks. Issue 2 (2020) - Feldman, Max; Cainelli, Gustavo; Kunzel, Gustavo; Muller, Ivan; Pereira, Carlos Eduardo
Abstract: The use of wireless networks in industrial environments is a reality today because of its advantages, but with the use of such networks, the problem of coexistence becomes inevitable. This paper presents a system to deal with the problems brought on by the networks coexistence, and thus avoid a reduction in the robustness of the network in which this issue has been accomplished. An adaptive channel mapping system is proposed in industrial wireless networks, where the affected channels are removed from the channel map used. A case study of the adaptive channel mapping system in a WirelessHART network is performed.